On-farm Evaluations of Wood-derived, Waste Paper, and Plastic Mulch Materials for Weed Control in Florida Container Nurseries - S. Christopher Marble; Shawn T. Steed; Debalina Saha; Yuvraj Khamare (HortTechnology, 2019)
Mulches have been evaluated extensively as a weed management tool in container plant production, but most research has focused on loose-fill wood-derived mulch materials, such as pine bark or wood chips. In this experiment, pine (mixed Pinus sp.) bark (PB), shredded hardwood (HW), and pine sawdust were evaluated for weed control and crop response both alone and in combination with a guar gum tackifier alongside a plastic film mulch, a paper slurry mulch, and the paper slurry mulch + PB and compared with a nonmulched, nontreated control and a single application of preemergence herbicide (oxyfluorfen + pendimethalin). Mulch materials were applied to nursery containers ranging from 7 to 25 gal at two different nurseries and at two research centers in central Florida in 2017 and 2018. Results showed that the plastic mulch provided more than a 90% reduction in hand weeding time and weed weight over a 6-month period, and similar control was achieved with PB, paper slurry + PB, and the HW treatment (64% to 91% reduction in weeding time and weed weight). No growth differences were observed with any mulch treatment in any species evaluated including ligustrum (Ligustrum japonicum), Chinese elm (Ulmus parvifolia), or podocarpus (Podocarpus macrophyllum).